1999
DOI: 10.1046/j.1365-2311.1999.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Social biology and sex ratios of the eusocial gall‐inducing thrips Kladothrips hamiltoni

Abstract: Summary1. Thrips comprise the only order besides Hymenoptera where females are diploid and males are haploid. This makes them useful insects for studying the roles of kin selection and ecology in social evolution.2. Kladothrips hamiltoni is one of six species of Australian gall‐inducing thrips that have been identified as eusocial. Galls are initiated by a single foundress, who rears her brood and remains within the enclosed gall for life. The adults of both sexes of her first brood cohort are morphologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…Our analysis however suggests that haplodiploidy, together with unmatedness, could have contributed to the evolution of exclusive female help in outbreeding species like eusocial Hymenoptera by lowering the benefit threshold female helping. In contrast to Hymenoptera, in eusocial haplodiploid thrips both male and female offspring participate in nest defense (Crespi 1992;Kranz et al 1999). The evolution of both male and female helpers in eusocial thrips may be linked to lack of pre-adapations in either sex to soldiering, as suggested by Ross et al (2013), but also to the high degree of ancestral inbreeding in these species (McLeish et al 2006), which reduces the importance of relatedness asymmetries (Chapman et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis however suggests that haplodiploidy, together with unmatedness, could have contributed to the evolution of exclusive female help in outbreeding species like eusocial Hymenoptera by lowering the benefit threshold female helping. In contrast to Hymenoptera, in eusocial haplodiploid thrips both male and female offspring participate in nest defense (Crespi 1992;Kranz et al 1999). The evolution of both male and female helpers in eusocial thrips may be linked to lack of pre-adapations in either sex to soldiering, as suggested by Ross et al (2013), but also to the high degree of ancestral inbreeding in these species (McLeish et al 2006), which reduces the importance of relatedness asymmetries (Chapman et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent analyses have shown that male workers should evolve as readily as female workers (Craig 1982;Pamilo 1991). Furthermore, eusocial haplodiploid thrips with both male and female helpers have been found (Crespi 1992;Kranz et al 1999). These findings and new analyses suggest that ecological circumstances and pre-adaptations like maternal care are more important in determining the sex of helpers than the genetics of sex determination (Queller and Strassmann 1998;Ross et al 2013).…”
Section: Introductionmentioning
confidence: 92%
“…In eusocial species, the first cohort to eclose are gall-bound soldiers, which are distinguished by robust forelimbs, reduced or absent wings, and self-sacrificing behavior exhibited in defense of the gall to the benefit of dispersing sisters and brothers (2,4,7). However, in at least one species, Kladothrips hamiltoni, it is suspected that soldiers could also be defending a few of their own offspring, as well as nieces and nephews, because soldiers are suspected of at least some egg laying within their natal gall (8). The foundress usually lives long enough to overlap with the adult soldiers, and she usually dies some time before the next group of individuals, the dispersive macropterae, reach the adult stage.…”
mentioning
confidence: 99%
“…Correlation coefficients with an asterisk (*) are significant at less than the 0.05 level Sex ratios vary among species, and they also exhibit a temporal variation, as one sex can be produced before the other. Among the social species studied in detail thus far, there are notable associations between the order of eclosion by sex in soldiers and three variables: soldier sex ratios, offspring sex ratios, and the extent of reproductive skew between female soldiers and foundresses (Kranz et al 1999(Kranz et al , 2001a(Kranz et al , 2001bChapman et al 2002). Thus, K. habrus and K. waterhousei exhibit protogynous (females first) soldier production, strongly female-biased soldier sex ratios, an unbiased sex ratio of reproductive dispersers, and relatively high skew.…”
Section: Evolution Of Sex Allocation Ecology Genetic Structure and mentioning
confidence: 98%